Type 2 diabetes - factors of occurrence and its complications - Żuchnik, Magda; Rybkowska, Agnieszka; Szczuraszek, Paulina; Szczuraszek, Hugo; Bętkowska, Paulina; Radulski, Jakub; Tomkiewicz, Michał; Paluch, Michał; Licak, Gabriela; Olko, Paweł (Quality in Sport, 2023)
Introduction Diabetes mellitus is a collective term for heterogeneous metabolic disorders, the main factor of which is chronic hyperglycemia resulting from a defect in insulin secretion or action. It affects the damage, dysfunction and performance of various organs. The aim of the study The purpose of this article is to discuss type 2 diabetes mellitus. Presentation of the mechanisms involved in it and the complications it causes in the various organs. Material and methods This review was based on available data collected in the PubMed data base. The research was done by looking through keywords such as: , type 2 diabetes”, , diabetic cardiomyopathy”, , diabetic nephropathy”, , diabetic neuropathy”, , diabetic foot”, , diabetic retinopathy”, , risk factors for type 2 diabetes”. Conclusions Many studies have shown that the presence of type 2 diabetes adversely affects the body. Type 2 diabetes increases the risk of organ complications, which significantly reduces the quality and shortens the life of patients. For that reason, care should be taken to reduce the incidence rate of this type of diabetes and to prevent and detect its complications early. Therefore, new initiatives and research should be undertaken to broadly understand the risk factors and mechanisms of developing type 2 diabetes complications.